Heterogeneous Amplitude−Phase Metasurface for Distinct Wavefront Manipulation. Issue 10 (5th August 2021) - Wang, Chaohui; Xu, He-Xiu; Wang, Yanzhao; Zhang, Cheng; Wang, Shaojie; Wang, Mingzhao; Yang, Xiao
Abstract : Achieving simultaneously multiple distinct wavefront manipulations using a single flat plate is pivotal in increasing the integration level and information capacity of an optoelectronic system. As of today, the state‐of‐the‐art metadevices have been devoted to multiple functionalities by imparting two independent phase patterns triggered at two orthogonal polarization states. However, in fact, it is terribly challenging to realize individual amplitude−phase ( A−P ) control using an anisotropic metasurface. Herein, a heterogeneous strategy for achieving an A−P manipulation utilizing heterogeneous indium tin oxide (ITO) resistive films and metal patterns is demonstrated. By synergizing dual‐layer ITO films and a sandwiched dual‐mode metallic layer on a back metallic ground, the proposed meta‐atom exhibits near‐zero and near‐unity reflections for dual‐orthogonal linear polarizations. The above feature can be utilized to trigger polarization‐dependent functionalities by uniformly and inhomogeneously distributing the ITO and metallic pattern, respectively. Using this proposed architecture, two metasurfaces with integrated radiation−absorption and integrated diffusion−absorption function are implemented. Both numerical and experimental results demonstrate that two well‐designed metadevices enable to achieve a similar broadband absorptivity (above 90% within 7.8−18.5 GHz) but completely distinct wavefront manipulations triggered by two polarizations. The heterogeneous metasurface concept paves the way toward realizing high‐performance multifunctionalities with complex wavefront manipulation capabilities. Abstract : Herein, a heterogeneous strategy for achieving an amplitude−phase ( A–P ) manipulation utilizing heterogeneous indium tin oxide (ITO) resistive films and metal patterns is demonstrated. Both numerical and experimental results demonstrate that two well‐designed metadevices enable to achieve a similar broadband absorptivity (above 90% within 7.8−18.5 GHz) but completely distinct wavefront manipulations triggered by two polarizations.